Eight-year Diet and Physical Activity Intervention Affects Serum Metabolites during Childhood & Adolescence : A Nonrandomized Controlled Trial - Zarei, Iman; Eloranta, Aino-Maija; Klåvus, Anton; Väistö, Juuso; Lehtonen, Marko; Mikkonen, Santtu; Koistinen, Ville M.; Sallinen, Taisa; Haapala, Eero A.; Lintu, Niina; Soininen, Sonja; Haikonen, Retu; et al. (Cell Press, 2025)
Long-term lifestyle interventions in childhood and adolescence can significantly improve cardiometabolic health, but the underlying molecular mechanisms remain poorly understood. To address this knowledge gap, we conducted an 8-year diet and physical activity intervention in a general population of children. The research revealed that the intervention influenced 80 serum metabolites over two years, with 17 metabolites continuing to be affected after eight years. The intervention primarily impacted fatty amides, including palmitic amide, linoleamide, oleamide, and others, as well as unsaturated fatty acids, acylcarnitines, phospholipids, sterols, gut microbiota-derived metabolites, amino acids, and purine metabolites. Particularly noteworthy were the pronounced changes in serum fatty amides. These serum metabolite alterations could represent molecular mechanisms responsible for the observed benefits of long-term lifestyle interventions on cardiometabolic and overall health since childhood. Understanding these metabolic changes may provide valuable insights into the prevention of cardiometabolic and other non-communicable diseases since childhood.